Growing a charity internationally - the use of social franchising as a model of replication - De-Wint, Stephen (2012)
The management project sets out to establish how the theory, practice and principles of social franchising can be used to aid growth and the improvement of quality within an existing charity. The work identifies the importance of the not-for-profit sector in helping to bridge the widening gap between available resources and social need. It identifies the need for not-for-profit enterprises to grow to fill this gap. It uses a case study approach of two existing international youth development charities to explore how principles of franchising have been used in the past and their applicability for the future. The project concludes that there is a ‘fit’ for franchising within the two organisations studied, that there is a need to address certain key issues such as standardisation, proof of delivery models, the vetting of franchisees, and the role of franchisor and franchisee within these modified processes. The project also identifies a number of topics for further research around monitoring and evaluation, development and use of ‘brand’ in the growth strategy and the potential benefits of a ‘mixed model’ franchising approach.